1997
DOI: 10.1046/j.1365-2702.1997.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of mothers caring for a child with severe atopic eczema

Abstract: Atopic eczema is a relatively common disease which frequently occurs during childhood. This paper reports the findings of a research study which explored the effects upon family life of caring for a child with severe atopic eczema. Seventy-seven accounts written by mothers of preschool children with this disease were analysed using qualitative latent content analysis. The focus of this paper is on the implications of the disease for the mothers' role and the additional work generated by the disease. The implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…[15][16][17][18] The present study shows that these issues are also pertinent to the milder case mix seen in primary care, where the vast majority of cases are managed. Qualitative studies in other healthcare settings have found accounts of carers feeling that doctors do not take eczema seriously and that they offer insufficient information.…”
Section: Comparison With Existing Literaturementioning
confidence: 75%
“…[15][16][17][18] The present study shows that these issues are also pertinent to the milder case mix seen in primary care, where the vast majority of cases are managed. Qualitative studies in other healthcare settings have found accounts of carers feeling that doctors do not take eczema seriously and that they offer insufficient information.…”
Section: Comparison With Existing Literaturementioning
confidence: 75%
“…2 Most studies on quality of life focus on assessing the quality of life of patients. Family quality of life has been explored in dermatology, [3][4][5][6][7][8][9] oncology, [10][11][12][13][14][15][16][17][18][19][20][21] and in the field of physical and mental disability, [22][23][24][25][26][27][28] but little is known about the impact of disease on families of patients in many other specialties. Several key review articles have been written concerning the impact of illness on the quality of life of the partner, 1 the impact of cancer on the family, 14,19 the carer burden in mental health illness, 22 the impact of chronic childhood illness on siblings, 29 and the impact of chronic disease in the elderly on the patient's family.…”
Section: Introductionmentioning
confidence: 99%
“…The nurse-parental relationship is associated with greater self-efficacy and maternal confidence in being able to manage children's AE. Studies have found that AE affects the quality of life of mothers and children living with AE, including in the aspect of developing a rapport with and gaining the trust of healthcare providers (Bridgeman 1994, Elliott & Luker 1997, Cheung & Lee 2011. Thus, good communication between healthcare providers and the parents is essential.…”
Section: Introductionmentioning
confidence: 99%